MENGATASI KEBIASAAN BERMAIN GAME ONLINE MELALUI KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT - Silva Zelika; Masturi Masturi; Santoso Santoso (Universitas Muria Kudus, 2022)
This study aims to: 1) describe the factors that cause the habit of playing online games in seventh grade students of SMP Negeri 2 Gebog Kudus. 2) Helping overcome the habit of playing online games through behavioristic counseling with Self Management techniques for seventh grade students of SMP Negeri 2 Gebog Kudus.Based on the results of the study, it can be concluded that the factors that cause the habit of playing online games are two factors, namely internal and external, there are several factors that cause CNKA and MHAR to have the habit of playing online games, including: lack of self-control within the counselee, so CNKA and MHAR do not anticipate negative impact arising from playing online games excessively and continuously. The counselee has a habit of playing online games from the counselee's environment that is less controlled, because he sees many of his other friends playing online games. After counseling with a behavioristic approach and self-management techniques, CNKA and MHAR were able to eliminate their maladaptive behavior and were able to manage themselves well.